Potniški center Ljubljana - Nikšič, Matej (Urbani izziv, 2002)
The competition was organised with the desire to stop the futile quest in which design of the transport knot in Ljubljana and all connected projects, has found itself. Following changed social and political circumstances and theinternational tender for participation, one hoped for fresh solutions unhindered by local disputes. However not many such solutions were received, even because of the conceptually rather rigid competition guidelines and technical regulations. In the given circumstances the presented proposals offered solutions to the basic issues at hand, but they didn't bring any new initiatives for the given area, which has substantial city-building potential.
Keywords: architecture; arhitektura; avtobusne postaje; cestni promet; Ljubljana; prometna ureditev; prostorsko planiranje; spatial planning; urbanistično planiranje; železniške postaje; železniški promet